2006
DOI: 10.1038/sj.onc.1209453
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of NPM in myeloid leukemias is dictated by gain-of-function mutations that create a functional nuclear export signal

Abstract: Nucleophosmin (NPM) is a nucleus-cytoplasmic shuttling protein that is implicated in centrosome duplication, cell cycle progression and stress response. At the steady state, NPM localizes mainly in the nucleolus, where it forms a complex with different cellular proteins. One-third of acute myeloid leukemias (AML) are characterized by aberrant cytoplasmic localization of NPM, due to mutations within its last coding exon (exon 12) that cause a frameshift and the formation of novel C-termini. We report here our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 14 publications
(15 reference statements)
2
45
0
Order By: Relevance
“…The above findings further support the concept that NPM1 mutants are 'born to be exported', 26 as it is suggested by the findings that (i) rare truncated mutants generated by mutations at exon 9 or 11 also acquire a new C-terminus NES and localize in cytoplasm; [30][31][32][33] (ii) NPM1 leukaemic mutants retaining tryptophan 288 harbour a stronger C-terminus NES motif than mutants lacking both tryptophans 288 and 290, to ensure the most efficient cytoplasmic export; 26 and (iii) the capability of NPM1 mutants to dislocate to the cytoplasm is stable over time. 34,35 Thus, all the evidences to date point to natural selection of a mutational event on the basis of its ability to promote cytoplasmic dislocation of the resulting protein, pointing to this event as critical for leukaemogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…The above findings further support the concept that NPM1 mutants are 'born to be exported', 26 as it is suggested by the findings that (i) rare truncated mutants generated by mutations at exon 9 or 11 also acquire a new C-terminus NES and localize in cytoplasm; [30][31][32][33] (ii) NPM1 leukaemic mutants retaining tryptophan 288 harbour a stronger C-terminus NES motif than mutants lacking both tryptophans 288 and 290, to ensure the most efficient cytoplasmic export; 26 and (iii) the capability of NPM1 mutants to dislocate to the cytoplasm is stable over time. 34,35 Thus, all the evidences to date point to natural selection of a mutational event on the basis of its ability to promote cytoplasmic dislocation of the resulting protein, pointing to this event as critical for leukaemogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…[43][44][45][46] Several studies have provided evidence that a new leucine-rich NES created by the NPMc þ mutation promotes CRM1-dependent nuclear export of NPMc þ , thus resulting in accumulation of NPMc þ in the cytoplasm. [5][6][7]47,48 In the current study, we demonstrate that the redox-sensitive C288 generated by the NPMc þ mutation has an important role in regulating the cytoplasmic accumulation of NPMc þ . Mutation of C288 to alanine enables NPMc þ to remain in the nucleolus, suggesting that this cysteine residue may be sufficient to cause cytoplasmic localization independent of the loss of W288 and the acquisition of additional leucine-rich nuclear export motifs resulting from the C-terminal extension.…”
Section: Discussionmentioning
confidence: 86%
“…In a subsequent study, NPM1 mutations were found in 53% of CN-AML patients and were associated with a higher CR rate and longer EFS compared with non-mutated cases . Each of at least 40 different NPM1 mutations described to date causes not only loss of tryptophan residues 288 and 290 (or only 290) that are critical for nucleolar protein localisation, but also acquisition of an additional nuclear export signal motif at the C-terminus of nucleophosmin Mariano et al, 2006), that lead to abnormal localisation of nucleophosmin in the cytoplasm.…”
Section: Mutations Of the Ccaat/enhancer Binding Protein (C/ebp) Alpmentioning
confidence: 99%